Effectiveness of Onion Extract Gel on Surgical Scars in Asians - Kumutnart Chanprapaph; Somsak Tanrattanakorn; Penpun Wattanakrai; Pranee Wongkitisophon; Vasanop Vachiramon (Hindawi Limited, 2012)
Background. Onion extracts have been shown in vitro to accelerate wound healing. Results from clinical studies on surgical scars in Caucasians were disappointing. The aim of this study is to evaluate the effectiveness of onion extract gel in improving the cosmetic and symptoms of surgical scars in Asians. Patients/Methods. Twenty Asians who had new Pfannenstiel's cesarean section scars were recruited in this prospective double-blinded, split-scar study. Each side was randomly assigned treatment with onion extract gel or placebo at 7 days after surgery. The product was applied three times daily for 12 weeks. Subjects were evaluated at baseline and 4th and 12th weeks. Scar redness was assessed by calorimeter, scar height and pliability were assessed by blinded investigators, and scar symptoms and overall cosmetic improvement were assessed by subjects. Results. Sixteen subjects completed the study. A statistically significant difference between two sides of scar in terms of scar height and scar symptoms was found. There was no statistically significant difference in scar redness, scar pliability, and overall cosmetic appearance between two sides. Conclusions. The early use of topical 12% onion extract gel on Pfannenstiel's cesarean section scar in Asians resulted in the improvement of scar height and scar symptoms.